Harry Potter and the deathly hallows - Rowling, J.K. (New York : A. A. Levine Books, 2009)
Juvenile fiction.
Sequel to: Harry Potter and the Half-Blood Prince.
Keywords: England -- Juvenile fiction; Magic -- Juvenile fiction